EFFICACY OF A DIGITALLY DELIVERED PERSONALIZED ELIMINATION DIET FOR THE SELF-MANAGEMENT OF INFLAMMATORY BOWEL DISEASE AND IRRITABLE BOWEL SYNDROME. (22nd January 2022) - Jactel, Samuel; Olson, Joseph; Brown, Jordan; Wolin, Kathleen; Jagiella, Valerie
Abstract: BACKGROUND: A large majority (60-80%) of Inflammatory Bowel Disease (IBD) and irritable bowel syndrome (IBS) patients report that symptoms originate from, or are exacerbated by "trigger foods", and modify their diets to alleviate discomfort. Dietary interventions appear to be a reasonable complementary treatment to traditional clinical care. Despite demand, there is no consensus on what diet is best for IBD or IBS patients. Popular diets, such as the low-fermentable oligosaccharide, disaccharide, monosaccharide, and polyol diet (FODMAP) have notable limitations (e.g., implementation cost, length, complexity) and are not personalized to an individual. OBJECTIVE: The purpose of this study was to evaluate the feasibility, desirability, and impact on gastrointestinal symptoms and quality of life (QoL) of a digitally delivered personalized elimination diet for IBD and IBS patients. METHODS: This was a single-center open-labeled uncontrolled prospective cohort study. Participants were recruited online and were provided access to Agora Health, LLC's digital personalized nutrition tool (N=37; CD = 9, UC = 12, IBS = 16). Over a period of 9 weeks, participants followed Agora's 4-step elimination diet protocol: identification, elimination and reintroduction of trigger foods, followed by a maintenance phase. At baseline, daily, and at conclusion, symptom scores were calculated. The Patient-Based Simple Clinical Colitis Activity Index (P-SCCAI) and Mobile Health Index for Crohn's Disease (mHI-CD) were used to calculate IBD disease severity. The Irritable Bowel Syndrome Symptom Severity Score (IBS-SSS) was used to assess IBS symptomatology. In addition to IBD & IBS symptoms, participants provided qualitative assessments of energy, stress, physical activity, and QoL. RESULTS: The digital personalized elimination diet program improved symptoms and received strong positive reviews. Significant symptom improvement (p<0.05 two-tailed t-test, Bonferroni-corrected) was seen for 81% of participants at week 5 (phase 2) and persisted for 70% at week 9 (phase 4), measured by the relevant symptom severity score. Clinically significant symptom improvement (>25% reduction in P-SCCAI or mHI-CD scores, >35-point reduction in IBS-SSS) was observed in 78% of participants at week 5 and 62% at week 9. Ninety-five percent of participants felt more empowered and in control of their digestive health and 89% felt their quality of life improved due to the program. Sixty-two percent reported improved energy, 68% reported lower stress and 60% reported more physical activity after completing the program. Daily engagement was seen for 95% of participants and 92% were satisfied with the program. CONCLUSIONS: Dietary elimination can improve symptoms in patients with IBD and IBS and digital tools can improve adherence and engagement. Randomized controlled trials are warranted.